2017
DOI: 10.1002/hon.2393
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution detected with conventional cytogenetic analysis is a potent prognostic factor in adult patients with relapsed AML

Abstract: We retrospectively investigated 144 patients with relapsed acute myeloid leukemia (AML) to clarify predisposing factors and the prognostic impact of acquisition of additional cytogenetic abnormalities (ACA) at the first relapse. Additional cytogenetic abnormalities are recognized as clonal evolution at the cytogenetic level. Fifty-nine patients (41%) acquired ACA at the first relapse. The incidences of ACA acquisition varied depending on cytogenetic abnormalities at initial diagnosis. Multivariate analysis ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…A previous study in AML provided a contrary prediction, which in an analogous manner defined the clonal evolution as additional cytogenetic abnormalities, and observed a worse prognosis. 37 Our prediction agrees with reported findings in NPM1 - mutated AML, 14 whereby AML patients with clonal evolution ( NPM1 - ) at relapse have a significantly longer remission duration than patients without clonal evolution ( NPM1 + ). The better prognosis associated with patients with new clones (AMA) might be due to the fact that the treatment has been effective in the basal clone.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study in AML provided a contrary prediction, which in an analogous manner defined the clonal evolution as additional cytogenetic abnormalities, and observed a worse prognosis. 37 Our prediction agrees with reported findings in NPM1 - mutated AML, 14 whereby AML patients with clonal evolution ( NPM1 - ) at relapse have a significantly longer remission duration than patients without clonal evolution ( NPM1 + ). The better prognosis associated with patients with new clones (AMA) might be due to the fact that the treatment has been effective in the basal clone.…”
Section: Discussionsupporting
confidence: 92%
“…It has been demonstrated that the extensive genetic abnormalities play an important role in the diagnosis, risk assessment, and determination of the prognosis of patients. According to the United States National Comprehensive Cancer Network (NCCN) guideline, the risk classification of AML can be divided into favorable, intermediate, and poor prognosis (5). However, in real clinical practice, many patients with favorable prognosis showed low sensitivity or no response to standard treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most common type of adult acute leukemia with an annual incidence of 3-8/10 5 (2). To date, cytogenetic analysis has been one of the most useful prognostic methods to classify AML Original Article patients into different prognostic risk groups (favorable, intermediate, unfavorable) (3). The cytogenetically normal AML (CN-AML), representing 40-50% AML patients, is the largest subset of de-novo AML cases (4,5).…”
Section: Introductionmentioning
confidence: 99%